Developing Dispossession: Infrastructure, Cultural Production and Legal Discourse in Treaty 3 - Barr, Caolan (2018)
This thesis examines how dispossession was produced for Anishinaabeg communities of Treaty 3 through interlocking processes of legal discourse, cultural production and development. It traces the genealogical origins of infrastructure through a series of dams built across Northwestern Ontario from 1871 until 1926. In Treaty 3, the discursive foundations for infrastructure and development were laid through a series of expeditions and legal decisions that justified and facilitated settler expansion. Likewise, development involved a set of mutually constitutive and reciprocal forms of epistemic, ontological, symbolic and material violence. In this work, I argue that dispossession is structural to settler colonialism and the defining feature which ties a set of seemingly disparate histories and processes together in Treaty 3. Recognizing gaps in the literature and colonial archive, I call for the development of new practices of inquiry that allow us to provincialize and unsettle the normativity of colonial violence and narratives. M.A.